Investigation of the process of coating formation during microarc oxidation of titanium - Zhassulan А.Ж.; Rakhadilov Б.К.; Baizhan Д.Р.; Shynarbek А.Б.; Ormanbekov К.Д. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
The structural and phase states of coatings formed on the surface of titanium by the method of microarc oxidation (MAO) are investigated. In the course of the study, a series of experiments were conducted with varying process parameters and electrolyte composition. Morphological and structural changes of the coatings were analyzed using various analytical methods, including electron microscopy and X-ray diffraction. Microarc oxidation of titanium was carried out in anodic potentiostatic mode for 10 minutes in various electrolytes based on phosphoric acid, sodium orthophosphate, potassium hydroxide and hydroxyapatite. After the MАO, the microgeometry of the surface does not change, i.e. a thin coating with a thickness of 5-7 microns is formed on the surface of titanium. The results of the examination of the coating surface by scanning electron microscopy showed that the coatings formed in an electrolyte with the addition of potassium hydroxide (KOH) have the most porous surface of all the coatings studied. The results of X-ray diffraction showed that anatase and rutile are the main phase in coatings. The composition of the electrolyte is one of the determining factors of the MАO process and is crucial for the application of MАO. The results of the study allow us to gain a deep understanding of the process of coating formation during microarc oxidation of titanium.